ANALISIS PENGENDALIAN KUALITAS DAGING DENGAN MENGGUNAKAN SEVEN TOOLS DI THE FOODHALL PLAZA INDONESIA - Trisno, Nico; Arnawisuda Ningsi, Besse; Arofah, Irvana (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aims to determine quality control, the most dominant types of defects, the causes of defects, and determine strategies to improve the quality of meat products at The Foodhall Plaza Indonesia. The data used is secondary data in the form of an existing database of goods received from May to June 2023 sourced from the Foodhall Plaza Indonesia SAP application, which will be analyzed using statistical aids in the form of control charts and seven tools, namely checking sheets, histograms, proportion control maps, process capability, Pareto diagrams, and fishbone diagrams. From the results of the analysis, it was found that the capability value of each product damage was negative, indicating that the process was not capable and outside the specification limits. Meat quality control at The Foodhall Plaza Indonesia is within control limits, where based on the Pareto diagram it is obtained that the dominant type of defect in product defects due to damaged packaging is 49.3%, black meat defects are 27.6%, and meat releases water by 23.1%, with the factors that cause defects coming from human resources, machinery, and work environment to work methods. Then, recommendations for quality improvement strategies are made, such as forming a quality control team; leaders always provide direction; enforce a reward and punishment system; and provide regular job training to improve skills and minimize errors